Hubungan Minat Membaca Buku-Buku IPS dengan Prestasi Belajar Siswa dalam Mata Pelajaran IPS di SDN 38/IX Jambi Kecil - Darmo Darmo (Universitas Batanghari Jambi, 2019)
This research is motivated by the symptoms of students' unwillingness to answer questions about the lessons given, it is caused by the unwillingness of students to memorize the subject matter and visit the library to read. Through this research will be revealed the relationship of interest in reading to student achievement in social studies subjects and at what level the relationship of the most dominant reading interest felt by students towards their learning achievement in social studies subjects. The relationship of reading interest that is intended in this study is limited to the influence, contribution and benefits of reading fondness towards learning achievement in social studies subjects felt by students in school, reading interest is a motivating force that encourages students to focus their attention on reading activities is very large towards learning achievement, in social studies subjects. So it is assumed students will have a great interest in reading as well. The research was conducted at 38 Negeri IX Jambi Kecil Elementary School on 52 class IV, V and VI students selected as a research sample, namely 50% of 104 population students. Data collection techniques used in this study were using a questionnaire consisting of 39 items given directly to 52 respondents as research samples. Questionnaire test results are administered as a group and analyzed using percentage techniques. Based on the results of the study revealed that: Classification of interest in reading social studies books students is an average of 72.15%. From this data it can be concluded that the classification of the most dominant reading interests is at a high level. 1) Classification of student achievement is in social studies subjects are at an average of 7.19 from this data it can be concluded that the classification of student achievement is the most dominant is at a high level. 2) The relationship of interest in reading social studies books on student achievement in social studies subjects is moderate, namely 0.638. This means that the correlation is adequate. The conclusions from the results of the study indicate that there is an adequate relationship between interest in reading social studies books and student achievement in social studies subjects at SD Negeri No. 38 / IX Small Jambi. So to all parties responsible for increasing interest in reading students, especially elementary school students No. 38 / IX Jambi Minor should motivate students to increase their interest in reading. Because the relationship of reading interest felt by students towards learning achievement in social studies subjects will be more meaningful if followed by real activities.